Development of TPACK-based E-Modules on Explant Sterilization and Somaclonal Diversity as Learning Media for Biology Students - Pasaribu, Bella Cronika; Fauziyah Harahap (Universitas Negeri Semarang, 2025)
This study aims to determine the feasibility of TPACK-based E-Modules on the subject of Explant Sterilization and Somaclonal Diversity as learning media for biology students. The assessment is conducted based on evaluations by subject matter experts, media experts, and learning experts. In addition, this study seeks to gauge the responses of lecturers and students to the developed E-Modules and to test their effectiveness. This research utilizes a Research and Development (R&D) methodology following the 4D model, which includes the stages of defining, designing, developing, and disseminating. The effectiveness of the TPACK-based E-Module was assessed using N-Gain analysis. The results of the study indicate that the feasibility of the E-Module, according to subject matter experts, is rated at 85.83% (very valid), media experts at 82.79% (very valid), and learning experts at 92.75% (very valid). Faculty responses achieved an average percentage of 91.72% (highly feasible). Student responses were divided into three stages: individual trials at 93.05% (highly feasible), small group trials at 89.58% (highly feasible), and large group trials at 91.97% (highly feasible). Based on the N-Gain test, a value of 0.69 was obtained, which falls into the moderate category. Therefore, the developed TPACK-based E-Module is deemed suitable and sufficiently effective for use as a learning medium for biology students.